Maximum Quasi-Static Indentation Stress Analysis of Flax/Epoxy and Glass/Epoxy Polymer Composites - Shahrul Azhar, Ilya Izyan; Jumahat, Aidah; Abdul Rahman, Noor Leha; Khiari, Ramzi; Abd Nasir, Muhammad Afnan Jamal (International Journal of Integrated Engineering, 2022)
The use of fibers is growing every day to meet the demands of the industry. Both synthetic and natural fibers offer benefits and drawbacks that are best suited to specific applications. Synthetic fibers are preferable to natural fibers because they have greater mechanical properties. However, in their application, synthetic fibers have a negative influence on the environment as they are not biodegradable. As a result, natural fibers as an alternative will reduce the environmental impact, though their properties are not as good as synthetic fibers. ANSYS APDL, one of the FEA software analysis, is used to perform quasi-static indentation (QSI) tests in this research work. The purpose of this study is to determine the influence of fiber orientations of 0°, 15°, 30°, 45°, 60°, 75°, and 90°, as well as the effect of the supporting ply angle, 0°, on the mechanical properties of Flax FRP composite. For layup sequences of [(+?,-?)2]S and [(±?)2,04]S, it was observed that maximum strength increases from 0° to 90° fiber orientation. Meanwhile, in a QSI test, the highest strength of Flax FRP was found at 45° for both [(+?,-?)2]S and [(±?)2,04]S layup sequences, with 94.20 MPa and 96.80 MPa respectively. The effect of fiber volume fraction, such as Glass FRP composites with fiber volume fractions of 30% and 60% shows that the fiber volume fraction for 60% has a better performance than 30%. Therefore, composites with a higher fiber volume fraction show better maximum strength and lower deformability. The results of modeling and simulation work on Flax FRP composites can aid in the development of new materials that are more sustainable than conventional techniques by anticipating the mechanical behavior of natural FRP composites.